Morphology-dependent binder-free CuNiO2electrode material with excellent electrochemical performances for supercapacitors. (December 2019) - Song, Chang-Seob; Gopi, Chandu V. V. Muralee; Vinodh, Rajangam; Sambasivam, Sangaraju; Kalla, Reddi Mohan Naidu; Obaidat, Ihab M; Kim, Hee-Je
Highlights: Binder-free nanosheet-like CuNiO2 electrodes on nickel foam are constructed with an aid of NH4 F. The amount of NH4 F is greatly influence the morphology of CuNiO2 material. Nanosheet-like CuNiO2 provides abundant active sites for Faradaic redox reactions. The optimal CuNiO2 exhibits high specific capacity, good rate capability, and excellent cycling stability. Abstract: Rational design for structure and morphology of multi-component metal oxides is an efficient and promising way to enhance energy storage performance of electrode materials. In this present work, nanosheet-like CuNiO2 heterostructures are fabricated using facile one-step hydrothermal route by introducing various amounts of ammonium fluoride (NH4 F) as structure-directing agent. The NH4 F assisted synthesis of CuNiO2 materials on Ni foam current collector can be effectively utilized as binder-free battery-type electrode materials for supercapacitors. With an assistance of NH4 F, the structural, morphological and composition evolutions of CuNiO2 electrodes are discussed effectively using X-ray diffraction, scanning electron microscopy and transmission electron microscopy and X-ray photoelectron spectroscopy characterizations. The CuNiO2 electrode material prepared with 0.4 M NH4 F provides large number of active sites, superior conductivity and rapid charge transfer, which are promote fast Faradaic redox reactions. As a battery-type material, the optimized 0.4-CuNiO2 electrode material (NH4 F is 0.4 M) exhibits a high specific capacity (~153.02 mA h g −1 at 2 A g −1 ), excellent rate capability (~87.4% retains even at 10 A g −1 ), and outstanding cycling stability (~94.14% at 6 A g −1 over 3000 cycles), respectively. Thereby, this study paves the path into rational design for structure and morphology of multi-component metal oxides for improving energy storage performance. Graphical abstract: Image, graphical abstract